Kenya : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria: Staff Report; Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper describes Kenya's third review under the three-year arrangement under the Extended Credit Facility (ECF) and request for modification of performance criteria. The Executive Board approved a three-year ECF arrangement for Kenya on January 31, 2011, which has been augmented on December 9, 2011 for a total of SDR 488.520 million. The authorities' primary fiscal balance outcome was in line with the program and consistent with a decline in the government debt-to-GDP ratio. Implementation of structural benchmarks has overall proceeded as expected.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet